The role of women in mass peasant protests under total collectivisation and the Holodomor in Ukraine - Romanets, Natalia (Ukrainian Peasant, 2025)
Abstract. The purpose of the article is to study the role of women in mass peasant protests during the period of total collectivization and the Holodomor in Ukraine. The scientific novelty of the research results lies in the highlighting of the causes, scale, features and consequences of mass women’s peasant protests during total collectivization and the Holodomor, and the repressive measures applied to their participants. Conclusion. Mass women’s protests were the main form of active peasant resistance during the period of total collectivization and the Holodomor in Ukraine. Mass peasant women’s protests of 1928–1932 against dekulakization, collectivization, and grain procurement were called riots, rebels, «women’s riots» and «volinka» in documents of the OGPU, the GPU of the Ukrainian SSR, judicial bodies, party and Soviet documents. The authorities explained the active participation of peasant women in the «volinka» by «kulak influence», ignorance, women’s conservatism, the patriarchal nature of peasant society, «certain distortions of party policy» during collectivization and dekulakization, and the «excessively lenient attitude of the punitive authorities» towards participants in mass protests. In fact, the women’s protest was a reaction to the implementation of Stalin’s destructive agrarian policy, which threatened not only the well-being but also the very existence of peasant families, as evidenced by the events of 1932–1933. «Volinka» took place in the form of demonstrations, meetings, general peasant resistance to government officials and local activists, and collective attacks on state and collective farm facilities. The number of participants in «volinka» ranged from 50–60 to 1000–2000 people. «Volinka» could last from several hours, a day, to several days. Women’s protests were characterized by organization, persistence of resistance to local authorities. During «volinka» peasant women were often armed with pitchforks, stakes, and knives. Women’s protests were accompanied by physical violence against collective farm, party and Soviet leadership, police officers, activists, and collective farmers, and the destruction of village councils, collective farm boards, and other institutions. Each specific «volinka» did not pose any real threat to the regime of that time. The scale of the peasant protests was dangerous, because in the first months of 1930 (January–March) the «volinka» covered most of the villages of Ukraine. The serious attitude of the authorities towards mass women’s protests is evidenced by the fact that armed detachments of the GPU and the police were used to suppress the largest and longest ones